2019
DOI: 10.1038/s41419-019-1408-5
|View full text |Cite
|
Sign up to set email alerts
|

ER stress sensor, glucose regulatory protein 78 (GRP78) regulates redox status in pancreatic cancer thereby maintaining “stemness”

Abstract: Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) signaling have been shown to be dysregulated in multiple cancer types. Glucose regulatory protein 78 (GRP78), the master regulator of the UPR, plays a role in proliferation, invasion, and metastasis in cancer. Cancer stem cells (CSCs) make up a crucial component of the tumor heterogeneity in pancreatic cancer, as well as other cancers. “Stemness” in pancreatic cancer defines a population of cells within the tumor that have increased ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 56 publications
1
69
0
Order By: Relevance
“…Additionally, in head and neck squamous cell carcinoma, the GRP78/p-PEK/NRF2 signaling pathway was found to promote the Warburg effect (domination of glycolysis over oxidative phosphorylation), being critical for the maintenance of both low ROS levels and the CSC-like phenotype in tumor-initiating cells [235]. Studies of the effects of shRNA/GRP78 on pancreatic cancer cells have revealed that GRP78, as the ER stress sensor and redox regulator, promotes self-renewal and tumorigenicity while preventing oxidative stress and thus maintaining cancer stemness [236].…”
Section: Intracellular Grp78mentioning
confidence: 99%
“…Additionally, in head and neck squamous cell carcinoma, the GRP78/p-PEK/NRF2 signaling pathway was found to promote the Warburg effect (domination of glycolysis over oxidative phosphorylation), being critical for the maintenance of both low ROS levels and the CSC-like phenotype in tumor-initiating cells [235]. Studies of the effects of shRNA/GRP78 on pancreatic cancer cells have revealed that GRP78, as the ER stress sensor and redox regulator, promotes self-renewal and tumorigenicity while preventing oxidative stress and thus maintaining cancer stemness [236].…”
Section: Intracellular Grp78mentioning
confidence: 99%
“…Given the roles of GRP78 in regulating PI3K−Akt activity and endoplasmic reticulum (ER) oxidative stress [13,21], we next examined whether induced targeting of PTEN with p85α in the lipid raft membranes by TSWU-BR4 was associated with delocalization of GRP78 from the membrane to the cytosol. Flow cytometric analysis showed that the cell surface localization of GRP78 was suppressed, which was associated with an increased level of cytosolic GRP78 by TSWU-BR4 ( Figure 4A and Supplementary Figure S1).…”
Section: Tswu-br4-induced Dissociation Of Grp78 and P85α Leads To Thementioning
confidence: 99%
“…ER is also recognized as a major site of the biosynthesis of cholesterol and lipids [17], as evidenced by involvement of GRP78 in regulating lipid metabolism of cancer cells and its localization in ER [18]. Additionally, GRP78 modulates antioxidant activities of glutathione and NAD(P)H:quinone oxidoreductase by inducing activation of protein kinase RNA-like endoplasmic reticulum kinase and nuclear factor erythroid 2 p45-related factor 2 [19], contributing the protection of cancer cells from oxidative stress-induced damage [20,21]. Increased formation of cell surface GRP78−PI3K complexes in cancer cells confers a beneficial effects on cell survival and resistance to reactive oxygen species (ROS)-induced lipotoxicity [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…As a broad specificity molecular chaperone within ER, binding immunoglobulin protein (Bip), also known as 78-kDa glucose regulated protein (GRP78), correctly folds nascent polypeptides and regulates the unfolded protein response (UPR) ensuring protection of the cell from denatured protein and reinforcing its anti-apoptotic role, when the cell is under stress 11 . In addition, Bip is responsible for maintaining "stemness" in cancer cells 12,13 . To demonstrate the mechanism of GSCs resistance to IR-induced ICD, the role of Bip was evaluated in ER stress-activated ICD.…”
Section: Introductionmentioning
confidence: 99%